Intimate Partner Violence; Are Saudi Physicians in Primary Health Care Setting Ready to Identify, Screening, and Respond? - Alsalman Z; Shafey M; Al Ali L (Dove Medical Press, 2023)
Zaenb Alsalman,1 Marwa Shafey,2 Laila Al Ali3 1Departments of Family and Community Medicine, College of Medicine, King Faisal University, Al Ahsa, Saudi Arabia; 2Department of Family and Community Medicine, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 3Ministry of Health, Dammam, Saudi ArabiaCorrespondence: Zaenb Alsalman, Departments of Family and Community Medicine, College of Medicine, King Faisal University, Po Box 3311, Al Ahsa, 36346, Saudi Arabia, Tel +966545611633, Email Alsalman.zainab@hotmail.com; zalsalman@KFU.edu.saIntroduction: Intimate partner violence (IPV) is a growing hot topic in Saudi Arabia and primary health care (PHC) physicians play a significant role in preventing it. Our objective was to assess the PHC Physicians' readiness and barriers to identify, screen, and respond to IPV in Saudi Arabia.Methods: A cross-sectional study recruited physicians working in PHC centers in Saudi Arabia. Data was collected using a modified online self-administered questionnaire based on the PREMIS "The Physician Readiness to Identify and Manage IPV." The questionnaire consisted of respondent profile, perceived preparedness and knowledge, actual knowledge, practice issues, and opinion regarding barriers.Results: Among 169 PHC physicians, 60.9% had never experienced any formal IPV training. Around one-fifth of participants have a good perceived and actual knowledge, whereas one-third have a good perceived preparedness. Nearly half of the participants (46.7%) do not screen for IPV and two-thirds of them (66.3%) have never identified an IPV case during the previous 6 months. The logistic regression model showed that family physicians were 2.27 times more likely to have a good knowledge than a general practitioner, and participants with IPV training were more likely to have a good level of perceived preparedness, perceived knowledge, and more likely to perform screening of IPV.Conclusion: The low level of PHC physicians' readiness to identify and respond to IPV is worrisome. Findings emphasize the urgent need for an IPV training program, a supportive work environment, and a clear referral system in order to help the practitioner to provide comprehensive services and ensure safety plans for abused women.Keywords: intimate partner violence, primary health care, women, family physicians, Saudi Arabia